Designing language courses : a guide for teachers - Graves, Kathleen (London : Heinle & Heinle, 2000)
Designing Language Courses: A Guide for Teachers is a clear and comprehensive overview of course design. This text provides a practical guide to designing language courses by encouraging teachers to explore ways of planning and organizing content, and evaluating materials.
A Systems Approach to Course Design -- Defining the Context -- Articulating Beliefs -- Conceptualizing Content -- Formulating Goals and Objectives -- Assessing Needs -- Organzing the Course -- Developing Materials -- Adapting a Textbook -- Designing an Assessment Plan.
Includes bibliographical references.
1
Keywords: Curriculum planning; Language and languages -- Study and teaching